Space charge modulation and ion current rectification of a cylindrical nanopore functionalized with polyelectrolyte brushes subject to an applied pH-gradient - Chen, Yue-Ting; Hsu, Jyh-Ping (Journal of colloid and interface science, 2022)
[Display omitted] •Electrokinetic behavior of cylindrical nanopores subject to an extra pH-gradient is modeled.•ICR performance depends highly on the level of applied potential bias, and is optimum at a medium strong pH gradient.•Influence of PE layer thickness on ICR performance is important only if pH gradient is medium strong.•The optimum ICR performance occurs at a medium thick PE layer (~3 nm)•The underlying mechanisms of the present novel system are investigated in detail for the first time. Considering versatile potential applications of bioinspired membranes, we simulate the electrokinetic behavior of a cylindrical nanopore, surface modified by a polyelectrolyte (PE) layer. Taking account of the effect of electroosmotic flow and an additionally applied pH gradient, the influences of the strength of the pH gradient, the PE layer thickness, the length of the nanopore and its radius on its conductance and ion current rectification (ICR) performance are assessed. We show that if pHU (the pH at the higher pH end of the nanopore) is fixed at 11 and pHL (the pH at the lower pH end of the nanopore) varies from 3 to 11, the rectification factor Rf has a local maximum occurring in 6 < pHL <8; the greater the magnitude of the applied potential bias |V| the smaller the pHL at which the local maximum occurs. The influence of the PE layer thickness on the nanopore rectification performance is important only if 5 < pHL <8, and the optimum performance is reached at a medium thick PE layer (ca. 3 nm). Possible mechanisms associated with the ion transport phenomenon under consideration are proposed and discussed in detail.